Apical Hypertrophic Cardiomyopathy Combined with Bilateral Renal Artery Stenosis in Leriche Syndrome: A Rare Coexistence - Kocatuerk, Hasan; Bayram, Ednan; Colak, Mehmet Cengiz; Karaca, Leyla (Forum Multimedia Publishing, Llc, 2008)
We describe the case of a 60-year-old male hypertensive patient who was admitted to our department with intermittent claudication. An echocardiography evaluation detected apical hypertrophy without an intracavity pressure gradient. Transthoracic echocardiography has been the first-line imaging method for patients with suspected hypertrophic cardiomyopathy (HCM), but the method's shortcomings in evaluating the apex are well known. Thus, images from the patient's magnetic resonance imaging and angiography examinations confirmed the classic features of apical HCM. In addition, a 3-dimensional computed tomography evaluation disclosed Leriche syndrome concurrent with severe bilateral stenosis of the renal arteries. Apical HCM combined with severe renal artery stenosis is very rare and has not previously been reported with Leriche syndrome.
Keywords: Internal Thoracic Artery; Patient